2006
DOI: 10.1109/twc.2006.05301
|View full text |Cite
|
Sign up to set email alerts
|

On the performance analysis of equal-gain diversity receivers over generalized gamma fading channels

Abstract: Abstract-A versatile envelope distribution which generalizes many commonly used models for multipath and shadow fading is the so-called generalized Gamma (GG) distribution. By considering the product of N GG random variables (RV)s, novel expressions for its moments-generating, probability density, and cumulative distribution functions are obtained in closed form. These expressions are used to derive a closed-form union upper bound for the distribution of the sum of GG distributed RVs. The proposed bound turns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 20 publications
0
49
0
1
Order By: Relevance
“…Otherwise, the maximum beneficial cooperation duration (N ) is limited. 19 In summary, the proposed novel C-DF scheme can dynamically trade-off transmission reliability with delay and the analysis has shown that a certain node connectivity density is required to achieve a cascading cooperation chain with an arbitrarily low extinction probability.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Otherwise, the maximum beneficial cooperation duration (N ) is limited. 19 In summary, the proposed novel C-DF scheme can dynamically trade-off transmission reliability with delay and the analysis has shown that a certain node connectivity density is required to achieve a cascading cooperation chain with an arbitrarily low extinction probability.…”
Section: Discussionmentioning
confidence: 93%
“…(3) and (4), the BER [19] in a point-to-point Rayleigh fading channel is given by Eq. (5), which is: Similarly, the BER for M quasi-static channels, that are combined by MRC is [17]:…”
Section: A M Channel Bit Error Ratementioning
confidence: 99%
“…Building sway causes misalignment (pointing error) between the transmitter and the receiver, therefore less optical power will be collected by the receiver which degrades the performance the FSO system. Many authors have investigated the performance of FSO systems using different statistical models [4][5][6][7][8][9][10][11][12][13][14][15][16] to describe the channel randomness and its effect on the received signal. It was shown by [9], that the double-Weibull probability density function (pdf) is an appropriate model to describe the signal irradiance under medium to strong turbulence channel strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the related works on MRC and EGC, a perfect carrier phase estimation of the incoming signal was mainly assumed [4,5,7]. However, only in [8,9] the influence of the imperfect estimation of the received signal phase to the EGC system performance was discussed.…”
mentioning
confidence: 99%